MyD88 signaling in T cells directs IgA-mediated control of the microbiota to promote health - Kubinak, Jason L. (Cell Host Microbe, 2015)
Altered commensal communities are associated with human disease. IgA mediates intestinal homeostasis and regulates microbiota composition. Intestinal IgA is produced at high levels as a result of T follicular helper cell (T(FH)) and B cell interactions in germinal centers. However, the pathways directing host IgA responses towards the microbiota remain unknown. Here, we report that signaling through the innate adaptor MyD88 in gut T cells coordinates germinal center responses, including T(FH) and IgA+ B cell development. T(FH) development is deficient in germfree mice and can be restored by feeding TLR2 agonists that activate T cell intrinsic MyD88 signaling. Loss of this pathway diminishes high affinity IgA targeting of the microbiota and fails to control the bacterial community, leading to worsened disease. Our findings identify that T cells converge innate and adaptive immune signals to coordinate IgA against the microbiota, constraining microbial community membership to promote symbiosis.